Growth, carcass and meat quality traits in beef from Angus, Hereford and cross-breed grazing steers, and their association with SNPs in genes related to fat deposition metabolism - Papaleo Mazzucco, J. (2016)
Grazing steers from Angus and Hereford breeds, their cross-breeds and a three-way cross-breed (Limousin × Angus–Hereford) were measured for growth, carcass and meat quality traits. Breed effects were studied, and the association of SNPs with fat deposition and fatty acid (FA) composition (leptin, melanocortin-4 receptor, stearoyl-CoA desaturase, FA synthase and thyroglobulin) was tested. Limousin cross-breed showed the greatest final body weight, ultrasound rib eye area, dressing percentage, carcass and leg length, and the lowest backfat thickness and intramuscular fat content. Genetic groups had similar pH, shear force, cooking loss, L* and b* and n-6:n-3 ratio. Meat from 1/2-Angus presented greater a* than Limousin cross-breed. Whereas Angus had the highest total SFA content, Hereford had the lowest total SFA and the highest total MUFA. Limousin cross-breed had greater content of several individual PUFAs, total PUFA, n-6 and n-3 FA than Angus and 1/2-Angus. Leptin and FA synthase were associated with some FAs, supporting their influence over fat metabolism for grazing animals.